2016
DOI: 10.1016/j.ajog.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Exercise during pregnancy in normal-weight women and risk of preterm birth: a systematic review and meta-analysis of randomized controlled trials

Abstract: Aerobic exercise for 35-90 minutes 3-4 times per week during pregnancy can be safely performed by normal-weight women with singleton, uncomplicated gestations because this is not associated with an increased risk of preterm birth or with a reduction in mean gestational age at delivery. Exercise was associated with a significantly higher incidence of vaginal delivery and a significantly lower incidence of cesarean delivery, with a significantly lower incidence of gestational diabetes mellitus and hypertensive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
131
1
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(154 citation statements)
references
References 23 publications
9
131
1
13
Order By: Relevance
“…Some previous studies have reported high risk of preterm delivery associated with exercise during pregnancy [60], but a recent meta-analysis did not find any association between aerobic exercise for 35–90 minutes 3–4 times per week and increased risk of preterm birth [61]. In the current trial two women in the exercise group had a preterm delivery, and we found no indication of this being related to participating in the exercise program.…”
Section: Discussioncontrasting
confidence: 70%
“…Some previous studies have reported high risk of preterm delivery associated with exercise during pregnancy [60], but a recent meta-analysis did not find any association between aerobic exercise for 35–90 minutes 3–4 times per week and increased risk of preterm birth [61]. In the current trial two women in the exercise group had a preterm delivery, and we found no indication of this being related to participating in the exercise program.…”
Section: Discussioncontrasting
confidence: 70%
“…More importantly, women in the exercise arm had higher occurrences of vaginal delivery and lower occurrences of gestational diabetes, and no differences in low birthweight, thus giving providers and patients additional evidence on the safety and benefits of exercise during pregnancy. 52 …”
Section: Practical Approaches To Assist Providers and Patients In Meementioning
confidence: 99%
“…In this context, an international expert committee recently reviewed the literature and provided specific exercise recommendations for elite athletes throughout pregnancy (Bo et al, 2016) and postpartum (Bo et al, 2017b). In general, physical activity and moderate exercise during pregnancy are found to be safe both for the mother and the child (Hellenes et al, 2015; Di Mascio et al, 2016), although 30–60% reduced training volumes during the third trimester has been reported in recreational and competitive runners (Potteiger et al, 1993; Bailey et al, 1998; Tenforde et al, 2015). …”
Section: Introductionmentioning
confidence: 99%